2015
DOI: 10.3340/jkns.2016.59.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid Hemorrhage Presenting with Seizure due to Cerebrospinal Fluid Leakage after Spinal Surgery

Abstract: Cerebrospinal fluid leakage may commonly occur during spinal surgeries and it may cause dural tears. These tears may result in hemorrhage in the entire compartments of the brain. Most common site of such hemorrhages are the veins in the cerebellar region. We report a case of hemorrhage, mimicking aneurysmal subarachnoid hemorrhage due to a cerebrospinal fluid leakage following lumbar spinal surgery and discuss the possible mechanisms of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Bozkurt suggested that elderly patients with hypertension and brain atrophy were more prone to SAH 4 . Canao believed that the risk of non-aneurysmal SAH in hypertensive patients was 2.6 times higher than that in control group 5 . Their report was also con rmed in our study, 73.9% of patients in the SAH group suffered from hypertension before surgery.…”
Section: Resultsmentioning
confidence: 94%
“…Bozkurt suggested that elderly patients with hypertension and brain atrophy were more prone to SAH 4 . Canao believed that the risk of non-aneurysmal SAH in hypertensive patients was 2.6 times higher than that in control group 5 . Their report was also con rmed in our study, 73.9% of patients in the SAH group suffered from hypertension before surgery.…”
Section: Resultsmentioning
confidence: 94%
“… 11 Regarding the CSF leak after spinal surgeries, a study published in 2019 concluded that the overall incidence of CSF leak after spinal surgeries involving resection of both intradural and extradural pathologies is relatively low (6.6%). 17 According to this review, we found that the volume ranged from 100 18 19 to 1,300 mL 20 with a mean volume of 521 mL. Another review showed that the mean volume of CSF drained, prior to the appearance of the symptoms of ICH, among 8 patients was 225 mL.…”
Section: Discussionmentioning
confidence: 89%
“…According to previous reports, intracranial hemorrhage secondary to spinal surgery is less infrequent than that secondary to craniotomy; the incidence of remote intracranial hemorrhage after craniotomy is approximately 0.08–0.6% ( 6 ) among included cases. Cevik et al and Bozkurt et al investigated 2,444 patients who underwent spinal surgery and found that only 0.08% of them developed intracranial hemorrhage postoperatively ( 7 , 8 ). Khalatbari et al determined that only four patients (0.37%) suffered this complication in a cohort of 1,077 cases ( 9 ), Pham et al found two patients (0.14%) in a cohort of 1,396 cases ( 10 ), and Floman et al reported three patients in a cohort of 1,196 cases ( 11 ).…”
Section: Discussionmentioning
confidence: 99%